Análisis de la afectación ambiental por actividades productivas sobre el recurso suelo en la subcuenca baja de casacay - Avila Vanegas, Luis Alberto (2018)
The research focused on the low sub-basin of Casacay, from 75 masl to 507 masl, where several representative activities of the studied sector are developed in order to help identify the environmental problems present in the soil, determining their current conditions and proposing a soil reuse comprising the concepts of sustainability and sustainability. The present investigative work raises the productive activities carried out in the Lower Sub-basin of Casacay such as vehicular transport, tourism, agriculture, livestock and artisanal mining etc., which produce negative impacts to the soil. Making the respective analysis, basic, heavy metal analysis, water analysis, and fruit analysis, to determine the soil condition where the main elements found are Cr, Cd and Pb, presents concentrations that significantly exceed the permissible limits being this the study approach developed within research. Each activity is influential in the Lower Subbasin of Casacay and all the impacts caused by the productive activities influence in a decisive way affecting the soil, one of the present problems is the high amount of lead within the resource, this being a non-biodegradable heavy metal has as a characteristic the accumulation and biomagnification through the ecosystem reaching affect the health of the people, productive economy and natural resources. In the productive part heavy metals are transported from the soil to the fruits reaching to contain the same levels of lead that are present in the soil.